Integrating Circular Economies: Enhancing Border Regions Environment and Public Health - Aloysius Hari Kristianto; Yuliana; Eddy Suratman; Akhmad Yani; Indang Dewata (Economics Development Analysis Journal, 2024)
The circular economy represents a groundbreaking economic model that transforming waste into valuable products, potentially benefiting regional and national economies. This research explores the correlation between household waste management and its impact on environmental degradation and public health. Employing the System Dynamics method, the study delves into the intricacies of real-world system behavior, examining causal links and interrelationships within a system of interconnected sub-systems. Utilizing mental data, including scientific publications, mass media news, and expert opinions, alongside quantitative time series, the research focuses on the limitations of household waste management in addressing air and water pollution, posing potential health risks. Findings indicate a connection between population growth and increased waste generation, predominantly from residential sources. Unmanaged waste creation threatens air and water quality, emphasizing the importance of waste management in minimizing pollutants for improved public health. Aligning with the circular economy's 3R concept, effective waste management not only mitigates environmental impact but also holds the potential to enhance income generation. The circular economy's recycling and green entrepreneurship promotion can stimulate investments, fostering job creation. Collaborative efforts between governments and business owners can further support distribution and marketing channels, encouraging local self-sufficiency